DIALECTICS OF THE CONCRETE AND HISTORICAL-CRITICAL PEDAGOGY IN BRAZIL - Newton Duarte (Universidade do Oeste Paulista, 2019)
Educational studies in Brazil have a strong tradition based on Marxist dialectical thinkers as Gramsci, Lukács and Kosik. One of the most significant Marxist approaches in the field of pedagogical theories in Brazil is called Historical-Critical Pedagogy. The non-critical educational approaches have been defending an almost immediate identification of the school contents and methods with the pragmatic needs emerged in everyday practices. This perspective ignores the dialectics phenomena-essence and takes the pseudo-concrete as the real concrete. Historical-Critical Pedagogy takes the opposite direction and understands that the way to engage school education in a transformative social praxis is to organize the school curriculum in order to provide the conceptual tools required to take the "detour" that Kosik, based on Marx, considered necessary for human beings to grasp the essence of social reality. This paper will be an attempt to explore the points of intersection between Dialectics of Concrete and Historical-Critical Pedagogy.